Orthodontic and Periodontic Concoction: A Review - Mishra, Sumita; Nanda, Smruti Bhusan (Orthodontic Journal of Nepal, 2015)
The article emphasizes on the need for amalgamation of orthodontic and periodontic treatment. The need arises when we need to respect the integrity of the periodontal apparatus enhancing the importance of oral health. The beauty of orthodontics in the long run is envisaged by the surrounding sound environment of gingiva. Orthodontic treatment is carried out in various stages: initial leveling and alignment, space closure and finishing, detailing respecting the force requirements, mechanics; different wires are being used to fit the various clinical situations. The periodontium needs to be in harmony to yield a successful orthodontic treatment outcome